2020
DOI: 10.1177/2633366x20967360
|View full text |Cite
|
Sign up to set email alerts
|

Rice straw powder/polylactic acid biocomposites for three-dimensional printing

Abstract: The research aim of this work was to understand the effects of the soil burial of rice straw on the morphology and properties of 3D-printed rice straw powder (RSP)/polylactic acid (PLA) biocomposites. The rice straw buried in the soil for various days was grounded and sieved into powder at 120 mesh. The RSP was then mixed with PLA at a mass ratio of 15/100 and the mixture was extruded into filament, followed by a fused deposition modeling 3D printing process. The as-prepared products were characterized in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…After being buried in soil for 180 days, the T i and T p values of PLA rose to 360.6 and 382.9 °C, respectively, while those of the ARP/PLA biocomposites increased to 339.9 and 368.2 °C, respectively. This trend is analogous to that of rice straw powder/PLA biocomposites [ 30 ]. After burial in soil, the components in the 3D-printed samples were easily degraded by water or microorganisms.…”
Section: Resultssupporting
confidence: 67%
“…After being buried in soil for 180 days, the T i and T p values of PLA rose to 360.6 and 382.9 °C, respectively, while those of the ARP/PLA biocomposites increased to 339.9 and 368.2 °C, respectively. This trend is analogous to that of rice straw powder/PLA biocomposites [ 30 ]. After burial in soil, the components in the 3D-printed samples were easily degraded by water or microorganisms.…”
Section: Resultssupporting
confidence: 67%
“…Yu et al [ 24 ] developed a new kind of environmentally friendly composite filament for FDM 3D printing based on RSP/PLA biocomposites, exploring the effects of the RSP size and pretreatment on the properties of the printed samples, when RSP was synergistically pretreated by alkaline and ultrasound, the composite exhibited the increased mechanical properties, thermal stability, and hydrophobic properties than untreated RSP/PLA. Yu et al [ 25 ] also experimented the effects of the soil burial of rice straw on the morphology and properties of 3D-printed RSP/PLA biocomposites, and they concluded that, more cavities with large holes could be observed on the surfaces of the samples with the extension of soil burial time of rice straw. As a result, the printed samples became more thermally stable when using buried rice straw while their mechanical properties became poorer due to the amplification of the cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Te rate of degradation of composites increased in an enzymatic environment [19]. Te soil burial of rice straw powder improves its thermal stability, but the mechanical properties of the composite get depressed [20]. With the addition of food and agricultural wastes such as Citrus limetta (mosambi), tea mill waste, wood four, and rice husk to suitable matrix materials such as epoxy, PLA, and polyester, they can be converted into useful materials.…”
Section: Introductionmentioning
confidence: 99%